Craniofacial morphology in children with van der Woude syndrome and isolated cleft palate. Issue 4 (August 2014) - Heliövaara, Arja; Karhulahti, Rekina; Rautio, Jorma
Abstract Objective : To compare cephalometrically 6-year-old children with van der Woude syndrome and cleft palate (VWS) to children with isolated cleft palate alone (CP). Design: A retrospective case-control study. Patients and setting: Forty-four children with VWS were compared to 73 children with CP using lateral cephalograms. The mean age of the children with VWS was 6.6 years (range = 5.9–8.2) and that of the children with CP, 6.2 years (range = 5.7–6.7). Palatal closure had been done at a mean age of 1.4 years (range = 0.8–2.2), mostly with the Veau-Wardill-Killner or the Cronin pushback surgical techniques. The data was collected over a 30-year period. Main outcome measure: Linear and angular measurements were obtained from lateral cephalograms. A Student's t-test was used in the statistical analysis. Results: The craniofacial morphology in children with VWS and CP was similar, but those with VWS had slightly smaller diameters of the lower pharyngeal airway. The maxilla and mandible were well related to each other, although a little retrusive in relation to the cranial base. The soft tissue profile reflected the skeletal relationships, no significant protrusion of the lower lip was noted. Conclusions: Six-year-old children with VWS and CP have similar craniofacial morphology.